2019
DOI: 10.1177/0363546519885359
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of Competitive Athletes Versus Nonathletes Undergoing Hip Arthroscopy for Treatment of Femoroacetabular Impingement Syndrome

Abstract: Background: A growing number of studies have examined return to sport in competitive athletes after undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS); however, few have evaluated the rate of achieving meaningful clinical outcomes in this group. Purpose: To determine if competitive athletes (professional, semiprofessional, or collegiate) have better 2-year patient-reported outcomes and achieve the minimal clinically important difference (MCID) and substantial clinical benefit at higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 48 publications
(54 reference statements)
1
46
0
Order By: Relevance
“…20,21,24 Furthermore, a study of 330 female patients undergoing hip arthroscopy for femoroacetabular impingement reported that female athletes have significantly greater rates of achieving the PASS and MCID when compared with those of nonathletes. 14 This is supported by a recent age-, sex-, and body mass index-matched study by Clapp et al, 6 who applied separate MCIDs to competitive athletes versus nonathletes and found that competitive athletes had higher rates of attaining the MCID as compared with those of nonathletes. While it is not practical to calculate a separate PASS or MCID threshold for every descriptive characteristic, we found that athletes in general require higher postoperative scores to ''feel good'' than nonathletes.…”
Section: Discussionmentioning
confidence: 87%
“…20,21,24 Furthermore, a study of 330 female patients undergoing hip arthroscopy for femoroacetabular impingement reported that female athletes have significantly greater rates of achieving the PASS and MCID when compared with those of nonathletes. 14 This is supported by a recent age-, sex-, and body mass index-matched study by Clapp et al, 6 who applied separate MCIDs to competitive athletes versus nonathletes and found that competitive athletes had higher rates of attaining the MCID as compared with those of nonathletes. While it is not practical to calculate a separate PASS or MCID threshold for every descriptive characteristic, we found that athletes in general require higher postoperative scores to ''feel good'' than nonathletes.…”
Section: Discussionmentioning
confidence: 87%
“…The improvements in PROMs in this study are in accordance with previous literature on athletes undergoing hip arthroscopy, although most studies include athletes in general and not only ice hockey players. 6,15,28,29 However, a previous study of 28 professional ice hockey players reported improved outcomes in the modified Harris Hip Score and high patient satisfaction postoperatively after arthroscopic treatment for FAIS. 25 Furthermore, Schallmo et al 31 noted high rates of return to the NHL and significantly higher return to sport (91%) as compared with professional basketball, baseball, and American football players.…”
Section: Discussionmentioning
confidence: 97%
“…29 Although several studies have reported positive results in elite athletes treated with arthroscopic surgery, most use return to sports (RTS) or performance outcome. 3,6,38 However, only a few studies have used patient-reported outcome measures (PROMs) to present the results, 10,36,37,39 and the reports on the long-or midterm outcome in this patient category are limited. 9,33 Nevertheless, arthroscopic treatment in athletes presenting with FAIS is increasing, and studies suggest that high-level athletes will improve their hip function and have a high rate of return to preinjury activity levels.…”
mentioning
confidence: 99%